2018
DOI: 10.3389/fpls.2018.01338
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic and in vitro Analyses of Arabidopsis Starch Synthase 2 Reveal Post-translational Regulatory Mechanisms

Abstract: Starch synthase 2 (SS2) is an important enzyme in leaf starch synthesis, elongating intermediate-length glucan chains. Loss of SS2 results in a distorted starch granule phenotype and altered physiochemical properties, highlighting its importance in starch biosynthesis, however, the post-translational regulation of SS2 is poorly understood. In this study, a combination of bioinformatic and in vitro analysis of recombinant SS2 was used to identify and characterize SS2 post-translational regulatory mechanisms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…However, until now it has not been clear whether SSIIa within this HEC is also phosphorylated or whether phosphorylation affects the catalytic activity of SSIIa or its interaction with other proteins. Phosphorylation of SSIIa in wheat endosperm amyloplasts and SS2 in Arabidopsis chloroplasts has been observed previously by Tetlow (2004) and Patterson et al (2018). In the present study, unlike previous investigations, SSIIa was immunopurified and shown to be substantially free from contamination by other starch synthases (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
“…However, until now it has not been clear whether SSIIa within this HEC is also phosphorylated or whether phosphorylation affects the catalytic activity of SSIIa or its interaction with other proteins. Phosphorylation of SSIIa in wheat endosperm amyloplasts and SS2 in Arabidopsis chloroplasts has been observed previously by Tetlow (2004) and Patterson et al (2018). In the present study, unlike previous investigations, SSIIa was immunopurified and shown to be substantially free from contamination by other starch synthases (Figure 1).…”
Section: Discussionsupporting
confidence: 73%
“…Despite lacking glycosyltransferase activity, the noncanonical starch synthase isoform AtSS5 promotes the initiation of chloroplast‐localized starch granules by providing a binding site for both glucans and myosine‐resembling chloroplast proteins (Abt et al ., 2020). By contrast, AtSS2 enzymatically elongates intermediate‐length glucan chains during the formation of starch granules and is regulated by phosphorylation from chloroplast casein kinases (CKII) (Commuri & Keeling, 2001; Patterson et al ., 2018). In response to oxidative stress, maltose is released from starch and metabolized into sucrose, which can then scavenge ROS in the cytosol (Thalmann et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…leaves), where starch is produced and degraded on a daily basis (Smith and Zeeman, 2020). Recent biochemical characterization of SS2 phosphorylation using phospho-ablative SS2 mutants (S63A and S65A) found no enzymatic or protein complex consequences to the loss of SS2 phosphorylation despite being phosphorylated by CKII; (Patterson et al, 2018)). Our data finds SS2 to be phosphorylated at Ser65; part of a canonical CKII phosphorylation motif ( pS [D/E][D/E][D/E]) (Purzner et al, 2018), exclusively at ZT0 in the rve 4 6 8 mutant.…”
Section: Discussionmentioning
confidence: 99%